PENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Sejahtra Sejahtra (Fakultas Ilmu Pendidikan Universitas Sari Mutiara Indonesia, 2021)
This study aims to determine the mastery of learning outcomes and the improvement of student learning outcomes after using the Jigsaw Type cooperative learning model in natural science subjects in Indonesia. The type of research is Classroom Action Research which is carried out in 2 cycles with steps ranging from: planning, implementing, observing and reflecting. The research was carried out at SD Negeri 043940 Perbesi with the research subjects being Class V students who opened 25 people. Data collection tool used to test learning outcomes. The data analysis technique used descriptive statistics by comparing the average value of 2 cycles. The results of the analysis in the first cycle, students completed as many as 17 people (68%) and 8 people (32%) students did not complete with an average value of 69.84. The results of the analysis in the second cycle, students completed as many as 22 people (88%) and students who did not complete as many as 3 people (12%) with an average value of 82.38. This shows that cycle II is stated classically. Based on the results of data analysis, it can be obtained that student learning outcomes are completely classical and improved by using the Jigsaw type cooperative learning model in science subjects for class V SD Negeri 043940 Perbesi.